The Implementation of Lesson Study in Learning English to Increase the Students’ Result to Students Offerings C in Malang University - Yuyun Bahtiar (Universitas KH. A. Wahab Hasbullah, 2019)
This study aims to find out how the application of Lesson Study and the results of Students’ Learning Offerings C in Malang University. This type of research uses C lassroom Action Research (CAR) using a descriptive-qualitative approach. The subject of the research was 28 students of Offerings C in Malang University. In this study shows that the application of Lesson Study through three stages, namely planning (Plan), implementation (Do), reflection (See) can improve student learning outcomes. The results showed that there was an increase in the application of Lesson Study which included the stages of planning (Plan), implementation (Do), reflection (See) and student learning outcomes from cycle I to cycle II, based on research data in cycle I and cycle II, experience an increase in success according to what is expected.